2021
DOI: 10.3390/microorganisms9050922
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of Vibrio Bacteria in the Winter Mortalities of the Critically Endangered Pinna nobilis

Abstract: Pinna nobilis populations, constituting the largest bivalve mollusk endemic to the Mediterranean, is characterized as critically endangered, threatened by extinction. Among the various factors proposed as etiological agents are the Haplosporidium pinnae and Mycobacterium sp. parasites. Nevertheless, devastation of the fan mussel populations is still far from clear. The current work is undertaken under a broader study aiming to evaluate the health status of Pinna nobilis population in Aegean Sea, after the mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…Despite its endangered status, P. nobilis populations are highly threatened by human activities, such as illegal fishing for commercial and consumption purposes [ 6 , 7 ]. However, significant mortalities, even extinction in some cases, of P. nobilis within its natural habitats are mostly due to various pathogen infections [ 8 ]. While records of this phenomenon began in 2016, it continues to devastate the populations of fan mussels to the present day [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its endangered status, P. nobilis populations are highly threatened by human activities, such as illegal fishing for commercial and consumption purposes [ 6 , 7 ]. However, significant mortalities, even extinction in some cases, of P. nobilis within its natural habitats are mostly due to various pathogen infections [ 8 ]. While records of this phenomenon began in 2016, it continues to devastate the populations of fan mussels to the present day [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…belonging to the Splendidus and Mediterranei clades were detected during mortality events in P. nobilis populations. Experimental laboratory conditions detecting the infection of P. nobilis by Vibrio spp have transformed the phenomenon of mortalities into a complicated matter [ 8 , 19 , 20 , 21 , 22 ]. Investigation of P. nobilis mortalities continued and more potential threats were implicated in the devastation of its natural populations [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Northern Europe and the Atlantic coast of the United States, heatwaves and warming sea temperatures (up to~1.5 • C over the past half-century) have been associated with long-term increases in abundance of certain pathogenic Vibrio spp., namely V. cholerae, V. parahaemolyticus, and V. vulnificus [21]. While it is worth noting that other Vibrio spp., such as Vibrio splendidus, express virulence factors at low temperatures [63], observed increases in Vibrio spp. abundance in Northern Europe and the US were associated with an unprecedented occurrence of environmentally acquired Vibrio infections in the human population [21].…”
Section: Vibrio Cholerae and Its Natural Habitatmentioning
confidence: 99%
“…as the likely cause (Darriba, 2017;Catanese et al, 2018). However, further research has indicated that other pathogens, such as bacteria from the genus Mycobacterium and Vibrio, were also involved (Carella et al, 2019;Šarić et al, 2020;Scarpa et al, 2020;Lattos et al, 2021). Moreover, according to these reports, the mass mortality events were presumably caused by polymicrobial disease associated with various abiotic factors, and the pathogenesis has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%